INTERPLAY AS A MECHANISM IN CONSTRUCTING ARCHITECTURE: SPATIAL NEGOTIATION IN PUBLIC SPACE OF KOTA TUA JAKARTA - Gaby Fitria Bahri; Kristanti Dewi Paramita; Yandi Andri Yatmo (Vitruvian : Jurnal Arsitektur, Bangunan dan Lingkungan, 2026)
This paper explores the understanding of interplay in architecture as a method of architectural design that negotiates two or more systems of order to generate new possibilities in spatial construction. Public space exists with various order systems that exist in a dominant or resistant way. However, this study argues that new space may exist through creative practice of play that enable interaction between orders. Interplay can be interpreted as a dynamic dialectic between systems of order that enable the construction of new spaces through spatial negotiation. This study explores interplay mechanisms to develop new architectural possibilities. The research was conducted through a case study of public spaces in Kota Tua Jakarta. This case study is selected due to the diverse and interacting systems of order present in the site. The study identifies six types of interplay in the public space: permanent-temporal, dynamic-static, formal-informal, dark-light, old-new, and attract-distract. Each interplay involves spatial operations of overlapping, occupying, spacing, adapting, and appropriation. By employing such approach, this paper offers architecture driven by interplay as a design method that negotiates the boundaries and dichotomies between systems of order, while also encouraging the production of more inclusive and dynamic spaces.